Polynomial versus similarity transformations between GPS and Turkish reference systems - Soycan, M (COMMONWEALTH ASSOC SURVEYING LAND ECONOMY, C A S L E, 2005)
Efforts to utilize GPS have increased and come a long way in recent years. GPS (Global Positioning System) is the most modern and reliable technique for surveying geodetic control networks. By using relative static GPS observation, it is possible routinely to obtain sub-centimetre positional accuracy for points in geodetic control networks. GPS uses WGS84 (World Geodetic System 1984) as its reference frame. Point position on the earth is obtained by GPS observation in this frame. However, in geodetic and engineering applications, different coordinate systems are used as local or national systems. Combination of GPS networks with the national coordinate system requires determination of the transformation parameters between WGS84 (or ITRF) and the relevant national coordinate system. Several models can be used for transformation. The main purpose of this research is examination of 2 and 3D polynomial transformation models instead of 2 and 3D similarity transformations for distorted networks. However, the study also aims to determine reliable transformation parameters between ITRF94 and Turkish National Reference frame ED50 for Istanbul.
Keywords: Engineering; Geology; Remote Sensing